Tinjauan Keselarasan Konstruktif pada Pengembagan Sistem Instruksional Unit Pembelajaran Analisis Cerpen di Kelas 9 - Fadhylah, Erlin; Wicaksono, Dirgantara (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This research evaluates the instructional system design of a ninth-grade short story analysis unit through a constructive alignment and cognitive depth audit. The study addresses a common issue in literary education, namely the gap between engaging learning activities and the expected depth of students’ analytical thinking. A descriptive qualitative research design was employed using document analysis techniques applied to lesson plans, learning activities, and assessment instruments. The evaluation was conducted using a constructive alignment matrix to examine the coherence between learning objectives, instructional activities, and assessment methods, as well as a Depth of Knowledge (DoK) checklist to assess the level of cognitive demand embedded in the unit design. The findings reveal that the instructional unit demonstrates a high degree of alignment between learning objectives and assessment components, with fifty percent of the total assessment weight allocated to students’ analytical abilities in identifying and interpreting intrinsic and extrinsic elements of short stories. However, the analysis also uncovers a cognitive gap between learning activities and assessment expectations. Learning activities are predominantly centered on educational games and recognition-based tasks, while the assessment instruments require higher-order thinking skills such as interpretation, synthesis, and critical evaluation. The integration of digital technology in learning activities is found to be effective in increasing student engagement and motivation. Nevertheless, the absence of explicit scaffolding strategies limits students’ ability to transition from surface-level recognition tasks to deeper literary analysis. Therefore, this study highlights the need for structured instructional scaffolding to ensure cognitive continuity and to support the development of higher-order analytical skills in literature learning.